2021
DOI: 10.1111/mec.16100
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, resilience, and functional redundancy of freshwater bacterioplankton communities facing a gradient of agricultural stressors in a mesocosm experiment

Abstract: Agricultural pollution with fertilizers and pesticides is a common disturbance to freshwater biodiversity. Bacterioplankton communities are at the base of aquatic food webs, but their responses to these potentially interacting stressors are rarely explored. To test the extent of resistance and resilience in bacterioplankton communities faced with agricultural stressors, we exposed freshwater mesocosms to single and combined gradients of two commonly used pesticides: the herbicide glyphosate (0-15 mg/L) and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 156 publications
3
9
0
Order By: Relevance
“…In phase II, when a single dose of 40 mg/liter glyphosate was applied to all mesocosms except for the phase II controls, a strong effect was observed in all ponds regardless of taxonomic resolution. These results are broadly consistent with our previous 16S rRNA gene amplicon sequencing from the same experiment, which showed community resilience to GBH pulses at higher taxonomic levels only ( 11 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In phase II, when a single dose of 40 mg/liter glyphosate was applied to all mesocosms except for the phase II controls, a strong effect was observed in all ponds regardless of taxonomic resolution. These results are broadly consistent with our previous 16S rRNA gene amplicon sequencing from the same experiment, which showed community resilience to GBH pulses at higher taxonomic levels only ( 11 ).…”
Section: Resultssupporting
confidence: 93%
“…Experiments conducted in diverse environments, such as soil and freshwater ( 9 11 ) and the bee gut microbiome ( 12 ), have shown that bacterial taxa from natural ecosystems vary in their sensitivity to glyphosate. Some of this variation is explained by the distribution of different EPSPS classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded physicochemical variables and water level weekly to track homogeneity across ponds. On 10 August 2016, we selected 48 ponds for a collaborative experiment to assess the responses of planktonic communities, including phytoplankton and bacterioplankton; see Fug ere et al (2020) and Barbosa da Costa et al (2021), respectively. Here we only report observations made over the first 43 d, as zooplankton communities were no longer sampled at the same resolution beyond this time point.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…We measured pesticides concentrations via liquid chromatography coupled to mass spectrometry (LC-HRMS) using an Accela 600-Orbitrap LTQ XL (LC-HRMS, Thermo Scientific) in the Department of Chemical Engineering at McGill University. The methods used are more extensively described in Fug ere et al (2020; glyphosate) and Barbosa da Costa et al (2021;imidacloprid). Briefly, we measured glyphosate via heated electrospray ionization in negative mode (mass range = 50-300 m/z [mass m per charge number z]), and imidacloprid in positive mode (mass range = 50-700 m/z).…”
Section: Laboratory Analysesmentioning
confidence: 99%